LIVROS, MEMÓRIA E CENSURA: UMA LEITURA DE “BIBLIOTECA MALDITA”, DA ARTISTA MARILÁ DARDOT - Castro, Deborah Walter de Moura (Revista (Entre Parênteses), 2025)
In different periods, books were collected or burned almost always as a ritualistic act of threat to the thinking of a people, an almost theatrical form of affront to memory, or a metaphorical possibility of killing or numbing cultures and societies. Since the end of the 20th century, the artistic world has seen a proliferation of works that address writing, books, libraries, and ruins, evoking monumental symbolism as a metaphor for memories and forgetfulness. In 2017, Brazilian artist Marilá Dardot exhibited the work/installation "Biblioteca Maldita", which consisted of 15 books written by women that were banned in Portugal during the dictatorial regime of Estado Novo. The aim of this work is to offer a reading of Dardot’s piece through the presence of books, writing, and based on concepts such as silence, memory and forgetfulness.